The Upstairs room - Reiss, Johanna (New York : Scholastic Inc, 1972)
A Dutch Jewish girl describes the two-and-one-half years she spent in hiding in the upstairs bedroom of a farmer's house during World War II.
Keywords: World War, 1939-1945 -- Personal narratives, Jewish -- Juvenile literature; Netherlands -- History -- German occupation, 1940-1945.; Jews -- Netherlands